The Development Of Mathematics In Philosophy And The School Of Formalism Contained In The Philosophy Of Mathematics. - Parandrengi, Mursyidah J (Aksioma Education Journal, 2024)
The philosophy of mathematics, with its many contradictions and paradoxes regarding systematic truths, contributes to the creation of a systematic and absolute foundation of mathematical knowledge, with the aim of preserving that foundation. This research aims to answer the question of what efforts are needed to overcome the crisis, contradictions and paradoxes in mathematics, as well as introduce the philosophical foundations of mathematics that are currently often used in the teaching and development of mathematics. The research method used is descriptive research using Systematic Literature Review (SLR). In particular, the emergence of formalism in mathematics education is also a reaction to formalism's attempt to impose the thinking of mathematicians on all humanity, thus forcing mathematics to be presented deductively. Therefore, as a suggestion, mathematics education should pay more attention to the diversity of abilities and potential of individual learners, realize that learners are not as smart as teachers, and that undergraduate and graduate students are not as smart as teachers.